VARIABLE INTER-ASSAY ESTIMATION OF SPERM DNA FRAGMENTATION IN STALLIONS CLASSIFIED AS GOOD AND BAD SEMEN FREEZERS - Ferreira, H. N.; Ferreira-Silva, J. C.; Rocha, J. M.; Farras, M. C. [UNESP]; Calixto, M.; Moura, M. T.; Alvarenga, M. A. [UNESP]; Oliveira, M. A. L. (Cryo Letters, 2018)
BACKGROUND: Semen cryopreservation causes DNA damage, thus requiring continuous monitoring. OBJECTIVE: To compare two assays for sperm DNA fragmentation (SDF) from stallions with contrasting semen freezability. MATERIALS AND METHODS: Thirteen stallions were classified as good semen freezers (GSF) or bad semen freezers (BSF). Ejaculates were cryopreserved with three diluents. Semen was subject to SDF evaluation using the sperm chromatin structure assay (SCSA) and Halomax (R) after thawing (0 h) and after a 4 h thermoresistance test. RESULTS: On semen of BSF, analysis by SCSA was similar between evaluations, but Halomax (R) showed increased SDF at 4 h. The GSF group was similar between time points in both assays. Diluents did not affect SDF, irrespective of the assay. Halomax (R) showed differences for BSF between time points, differently from SCSA. Linear regression did not show any correlation between assays. CONCLUSION: The use of Halomax (R) should be encouraged for sperm DNA fragmentation analysis in horse frozen-thawed semen, particularly under field conditions.
Keywords: reproduction; cryobiology; equine; spermatozoa